Sodium hypochlorite dental accidents. (February 2014) - Goswami, Mridula; Chhabra, Nidhi; Kumar, Gyanendra; Verma, Mahesh; Chhabra, Anuj
<x content-type="archive" xml:space="preserve">Abstract</x> Sodium hypochlorite is widely used in dentistry as an intra-canal irrigant, for debridement and to disinfect root canals. Although it is considered to be safe, serious mishap can result from its inappropriate use, and this has been reported infrequently in the literature. Two unusual cases of sodium hypochlorite toxicity and their successful non-surgical management are described in a 14-year-old girl and a 13-year-old boy.